ADAPTATION OF THE FARMERS' SKILLS TO THE REQUIREMENTS OF THE FUTURE AGRICULTURE - Anamaria Viorela GRAMA; Ștefan Laurențiu BĂTRÎNA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This research explores the evolving skill requirements in the agricultural sector, driven by changing business environments and technological advancements in the labour market. As agriculture undergoes significant transformation with the integration of technologies like drones, soil sensors, and data analytics, the role of farmers is shifting towards that of data-driven, business-savvy professionals. To assess modern agriculture's skill needs, the study employed a multi-faceted approach. Firstly, we utilized the European Skills/Competences, Qualifications and Occupations (ESCO) classification to identify agriculture-related skills. Secondly, we analysed job advertisements from Romanian profile websites to compare the skills mentioned in job postings with the ESCO taxonomy. Lastly, we administered questionnaires to agronomy students and practicing farmers to gauge their perspectives on necessary skills. The study revealed a comprehensive skill set relevant to agriculture, with a strong emphasis on information skills, effective communication, and management abilities. These findings highlight the multifaceted nature of contemporary agriculture careers, which require technical expertise, sales acumen, analytical skills, and adaptability to navigate the evolving landscape.